Penyuluhan Dan Penyegaran Pengetahuan Pasangan Suami Istri Tentang Metode Kontrasepsi Di Kelurahan Cimparuah - Novita Sari, nela (Jurnal Pengabdian Masyarakat, 2023)
According to WHO, 2018 Family planning is a way of enabling people to achieve the number of children they want and determine the spacing of pregnancies. The increase in population continues to increase, especially in developing countries, due to the high birth rate that occurs in developing countries due to the prevalence of low age of first marriage which is motivated by low education, low economy, relationships and traditions in society. Community Service is a medium to bridge the world of education with the community, where Higher Education is faced with the problem of how citizens / communities, especially the community in the STIKes Piala Sakti Pariaman fostered area, are able to overcome health problems in their environment. The purpose of this community service is mainly for cadres to be able to increase the reach of health services to married couples in the community and provide health information about contraceptive methods for married couples. The outcome of this activity is the increased knowledge of married couples about the importance of contraception to spacing children for the quality of the child.